Akselerasi Sistem Tol Laut Melalui Konsep Storage Island guna Pemberdayaan Wilayah Kecil Sebagai Pusat Logistik Berikat - Fazal Akmal Musyarri; Andriani Larasati; Paradisa Eksata Gheosa (Jurnal Archipelago, 2024)
The national development orientation is starting to lean towards marine-based development, to reduce regional growth disparities, especially in the Eastern Region of Indonesia. The government has set the Maritime State Concept as a development priority, where one of the five pillars of the concept is the development of maritime infrastructure and connectivity. The main focus in this concept pillar includes the idea of sea highways and policies in the national logistics system. The solution being developed by the government is to build a Bonded Logistics Center (PLB) as a multifunctional logistics warehouse to stockpile imported or local goods. However, currently PLB development is still focused on sea ports, land ports and industrial areas in several regions in Indonesia. This limitative implementation reduces the efficiency of implementing PLB in Indonesia. So the author recommends the grand design of "Storage Island" using a normative juridical writing method, with a statutory approach and a conceptual approach. Integration with the development of sea highways has resulted in several ideas in Storage Island, including: First, the use of coastal areas or small islands with an area of 2,000 km between sea toll routes as PLB; Second, time management related to transporting goods using cargo with TEU capacity, both large and small ships; The third is the separation of the sea toll route from the commercial route (passenger transport journeys) to the sea toll road and/or to Storage Island. The realization of a Storage Island requires a legal umbrella regarding the management of areas that are special islands for storing logistics goods, which can be realized by revising the Law on Management of Coastal Areas and Small Islands. It is hoped that the Storage Island idea can cumulatively reduce the cost burden on the national logistics system and make goods distribution time more efficient. The implication is equal distribution of economic development throughout Indonesia and supporting the realization of Indonesia as a maritime country.